2016
DOI: 10.1016/j.csbj.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Classification and substrate head-group specificity of membrane fatty acid desaturases

Abstract: Membrane fatty acid desaturases are a diverse superfamily of enzymes that catalyze the introduction of double bonds into fatty acids. They are essential in a range of metabolic processes, such as the production of omega-3 fatty acids. However, our structure–function understanding of this superfamily is still developing and their range of activities and substrate specificities are broad, and often overlapping, which has made their systematic characterization challenging. A central issue with characterizing thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Substrate specificity of O. tauri Δ6-DES DES specificity relies on intricate substrate features, including the acyl-chain position, length, unsaturation features, and the acyl-carrier nature (Heilmann et al, 2004a;Li, D et al, 2016). Domain swapping between DES of distinctive specificity, together with further amino acid mutation, could highlight the primary importance of His-Box and surrounding region for front-end desaturase activity and substrate specificity (Song et al, 2014;Li, D et al, 2016;Watanabe et al, 2016). However, neither the exact molecular features underlying DES (regio)specificity nor the hierarchical importance of the substrate features are yet clearly identified.…”
Section: Physiological Relevance Of Pδ6-des Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Substrate specificity of O. tauri Δ6-DES DES specificity relies on intricate substrate features, including the acyl-chain position, length, unsaturation features, and the acyl-carrier nature (Heilmann et al, 2004a;Li, D et al, 2016). Domain swapping between DES of distinctive specificity, together with further amino acid mutation, could highlight the primary importance of His-Box and surrounding region for front-end desaturase activity and substrate specificity (Song et al, 2014;Li, D et al, 2016;Watanabe et al, 2016). However, neither the exact molecular features underlying DES (regio)specificity nor the hierarchical importance of the substrate features are yet clearly identified.…”
Section: Physiological Relevance Of Pδ6-des Regulationmentioning
confidence: 99%
“…The discovery of plastidic Δ6-DES and the impact of their overexpression in O. tauri points out the requirement of tight regulation of the C18-PUFA pool in microalgae. (Lee et al, 2016;Li, D et al, 2016). The strategy used is this study further illustrates how overexpression in several host systems of distinctive glycerolipid composition gives insight into DES substrate specificity.…”
mentioning
confidence: 93%
“…DES specificity relies on intricate substrate features, including the acyl-chain position, length, unsaturation features, and the acyl-carrier nature (Heilmann et al ., 2004a; Li, D et al ., 2016). Domain swapping between DES of distinctive specificity, together with further amino acid mutation, could highlight the primary importance of His-Box and surrounding region for front-end desaturase activity and substrate specificity (Song et al ., 2014; Li, D et al ., 2016; Watanabe et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded “Further work to characterize these abundant proteins will be necessary” but could not give any new indication regarding head group specificity. [ 108 ]…”
Section: Head Group Variationmentioning
confidence: 99%